The DKMS-BMST Thalassemia program: Description, scope and impact - Nitin Agarwal; K. Jothi; Shalini Gambhir; Gabi Rall; Regina Landwehr; Lawrence Faulkner; Latha Jagannathan; Patrick Paul; Alexander H. Schmidt (Elsevier, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only established curative therapy for thalassemia. However, access to transplantation is constrained in limited-resource settings. Human leukocyte antigen (HLA) typing of patients and potential donors is one relevant barrier to allo-HSCT. Here we report on the DKMS-BMST thalassemia program. The program runs thalassemia camps where buccal swab samples are obtained from patients and potential family donors and HLA-typed free of charge. Since 2018, within the scope of the program, 390 camps have been conducted in India and 10,216 samples have been collected and HLA-typed. We are aware of 220 transplantations in patients of the program and are confident that the program makes a small but significant contribution to the cure of patients with thalassemia in India.